Analysing electrocardiographic traits and predicting cardiac risk in UK biobank. (June 2021) - Ramírez, Julia; Duijvenboden, Stefan van; Young, William J; Orini, Michele; Jones, Aled R; Lambiase, Pier D; Munroe, Patricia B; Tinker, Andrew
The electrocardiogram (ECG) is a commonly used clinical tool that reflects cardiac excitability and disease. Many parameters are can be measured and with the improvement of methodology can now be quantified in an automated fashion, with accuracy and at scale. Furthermore, these measurements can be heritable and thus genome wide association studies inform the underpinning biological mechanisms. In this review we describe how we have used the resources in UK Biobank to undertake such work. In particular, we focus on a substudy uniquely describing the response to exercise performed at scale with accompanying genetic information.